Analisa Sinyal Remote Control Untuk Aplikasi Pengendali Jarak Jauh - Randy Rahmanto; Belinda Ayuningtyas; Sulistyo Widodo (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
Indonesia's aerospace sector plays a crucial role in maintaining national sovereignty. However, the country's airspace is often infiltrated by irresponsible parties, necessitating an effective monitoring system. Unmanned radio-controlled helicopters are a potential solution, although they are limited in range. This study aims to design a long-range control system for radio-controlled helicopters using satellite phone communication, which offers wide coverage and can reach remote areas. The system comprises a remote control, a radio converter circuit, an audio mixer, and a satellite phone. The radio converter functions to transform the radio control signal frequency into its original frequency without a carrier frequency, which is then re-converted to be compatible with satellite phone input for signal transmission. Test results indicate that the system can transmit control signals with adequate frequency stability within the expected range. Despite minor oscillator instability at certain stages, the system overall operates as designed. In conclusion, this satellite phone-based control system effectively extends the operational range of radio-controlled helicopters and serves as a strategic solution for monitoring Indonesia's airspace.